Markovian approach to man-machine-environment systems - Alazawi, R. J. (ХНУРЭ, 2012)
The man-machine system including human being and environment is considered as a queuing system with respect to the How of incoming disasters, all considered models demonstrate markovian properties. The formulas for the system states probabilities are derived in the stable and non-stable cases.